Solution blow spun titania nanofibers from solutions of high inorganic/organic precursor ratio. Issue 2 (1st February 2018) - Santos, A.M.C.; Mota, M.F.; Leite, R.S.; Neves, G.A.; Medeiros, E.S.; Menezes, R.R.
Abstract: In this work titania nanofibers were produced from different precursor solutions by solution blow spinning. Hydrophilic polyvinylpyrrolidone, hydrophobic poly(vinyl acetate) and amorphous and semi-crystalline poly(lactic acid) polymers were used with green-solvents and titanium isopropoxide as the inorganic precursor. Hybrid nanofibers with high inorganic loading content were successfully produced from all precursor solutions. The fibers were calcined at different annealing temperatures for evaluation of phase transitions. The minimum temperature to obtain pure titania fiber was found to be 500 °C, as assessed by thermal characterization. Anatase was the unique polymorph formed at this annealing temperature. This is of paramount importance due to its photocatalytic character. Calcination at high temperatures showed that rutile slightly appeared at 600 °C for the polyvinylpyrrolidone-based system and showed a strong peak at 700 °C for all systems, co-existing with anatase as minor phase. The use of amorphous and semicrystalline poly(lactic acid) polymers did not influence the anatase crystal size and phase conversion. This was found to be dependent on the annealing temperature and medium acidity, as currently found in powder synthesis.